SUPPLY CHAIN OF CHANGES IN THE MUNICIPALITY OF HERCUL NDIA: EXPLORATORY ANALYSIS - Jorge, S. M.; Lourenzani, A. E.B.S.; Santos, C. V. (Revista Brasileira de Engenharia de Biossistemas, 2020)
Seedling production has been an important economic activity in the municipality of Herculândia since 1977. From the registration of the first nursery to presente day the production has presenetd great expansion, generating environmental benefits, job, new businesses and income. Thus, it is important to describe seedling agro-industrial system in terms of its organization and efficiency. This study aimed to characterize the seedling production chain in the municipality of Herculândia, describing the history and panorama of seedling production in the municipality, identifying the tiers that composse the chain in the region and describing the institutional and organizational environment. For that, an exploratory study was adopted, with the conduction of nine interviews for the collection of primary data.